What is life? : How Chemistry Becomes Biology - Pross, Addy (New York Oxford University Press, 2016)
Seventy years ago, Erwin Schroedinger posed a profound question: 'What is life, and how did it emerge from non-life?' Scientists have puzzled over it ever since. Addy Pross uses insights from the new field of systems chemistry to show how chemistry can become biology, and that Darwinian evolution is the expression of a deeper physical principle.
Include Index
Keywords: Biology--Philosophy -- Chemistry--Philosophy -- Biochemistry -- Biology